Management of Ground Water Hazard: A Case Study from Thar Coal Mines, Pakistan - Yasmin Nergis; Muhammad Jahangir Khan; Naeem A. Mughal; Mughal Shareef; Jawad Abdullah Butt (International Journal of Economic and Environmental Geology, 2018)
This study covers the Thar coal field block-II located in the southeast of Sindh, Pakistan. The aim of present study is to identify the impacts of ongoing coal mining activity on ground water quality and water table in community wells of villages in Thar coal mine block-II. The ground water samples from 58 community wells (located in 21 villages of block-II) were collected and analyzed for the water quality parameters like water table (depth), electrical conductivity/TDS, and pH. The groundwater samples from community wells and Gorano pond were analysed to assess water quality. The reserved area of Gorano pond is about 1500 acres, wherein water discharged from aquiufers in coal mining area of block-II is being accumulated. The extracted ground water is being disposed off in multiple depressions near villages Gorano, Kathar and Dhukar Shah.